Pengembangan E-Modul Berbasis Model Inquiry Based Learning Berbantuan Aplikasi Heyzine Terhadap Kemampuan Komunikasi Matematis Siswa - Firdatul Miranda; Fajriana; Nurul Afni Sinaga (FKIP Universitas Palangka Raya, 2025)
This study aims to develop an e-module based on inquiry-based learning model assisted by the heyzine application for students' mathematical communication skills on data centralization and data dissemination materials at SMP Negeri 3 Lhokseumawe. The background of this study is the low mathematical communication skills of students, the teaching and learning process still uses books and teaching modules that tend to be boring for student and many teachers are still unfamiliar with the use of applications such as heyzine. The method used is Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Product validation is carried out by media experts and material experts to determine the level of validity. Practicality and effectiveness are assessed through student response questionnaires and learning outcomes. The results showed that the validation of media experts obtained a score of 98.09%, and material experts 95.4% with the category of